A new species of Rhabdotalebra Young (Hemiptera: Cicadellidae: Typhlocybinae) associated with the guaran-guaran (Bignoniaceae: Tecoma stans L.) in Argentina - Paradell, Susana; Catalano, María Inés; Petrulevičius, Julián (Zootaxa, 2017)
The genus Rhabdotalebra Young is reviewed, including description of a new species, R. albinoi n. sp., from Buenos Aires province, Argentina. A detailed morphological description and illustrations of the new species are provided. A key of all known Rhabdotalebra species is provided to facilitate the comparison of the new species with those previously known, based on pattern coloration and male and female genitalia, is given. Some field observations on its biology are also provided.